Plastic melt molding machine / Mohammad Amir Jamil - Jamil, Mohammad Amir (2023)
The project is about a machine that can melt shredded plastic and molding it to make plastic extrusion. This project is based on a few problem statements such as the problem of having high cost of plastic injection machine. Then the need of having cash flow for students to make money by selling plastic extrusion to the market. The methodologies of this machine are to make plastic extrusion 4040mm by heating some shredded plastic inside the machine through a heating element and inject it by compressor into the mold by using the correct molding technique to make about o.5 m height of plastic extrusion. After the molding process it going to go through a cooling down process by cooling element which is water pump is used to provide flowing water to reduce the temperature of plastic extrusion. The significant of this project is to create a simple plastic injection machine to solve the problem statements stated and helping the small business to afford a small plastic injection machine. The expected result is a plastic extrusion about 0.5 m height and 40*40mm for length and width. The plastic extrusion is expected to use as a raw material in making a lot of furniture and other stuff.